Variation of platelet function in clinical phenotypes of acute venous thromboembolism – Results from the GMP‐VTE project - Panova‐Noeva, Marina; Wagner, Bianca; Nagler, Markus; Koeck, Thomas; ten Cate, Vincent; Eggebrecht, Lisa; Prochaska, Jürgen H.; Meyer, Imke; Gerdes, Christoph; Spronk, Henri M.; Lackner, Karl J.; ten Cate, Hugo; et al. (Journal of thrombosis and haemostasis, 2022)
Background The role of platelets in the pathogenesis of venous thromboembolism (VTE) is receiving increasing attention; however, limited information is available on platelet function in the acute phase of the disease. Objective To characterize platelet function according to VTE phenotypes. Patients/Methods In total, 154 subjects (isolated pulmonary embolism [iPE], n = 28; isolated deep vein thrombosis [iDVT], n = 35; DVT+PE, n = 91) were included. In this study platelet function analyzer (PFA)‐200, light transmission aggregometry (LTA), thrombin generation (TG) in presence (PRP) and absence (PFP) of platelets and platelet flow cytometry were investigated. LASSO regression was used to select clinical and platelet biomarkers that distinguish between VTE phenotypes. Results PFA‐200 results did not differ between VTE phenotypes. LTA from DVT+PE subjects showed lowest maximum aggregation after epinephrine and adenosine diphosphate compared to iPE and iDVT. Lower % of PAC‐1‐positive platelets after in‐vitro trigger were present in DVT+PE and iPE compared to iDVT. TG in PRP had lower peak height and velocity in DVT+PE and iPE against iDVT. The results of LASSO regression for the distinction between DVT+PE vs iDVT identified 18 variables (AUC =0.93) of which 72% were platelet biomarkers. For distinction between iPE and iDVT, 10 variables were selected (AUC = 0.96) of which 50% were platelet‐related. Obesity was the only variable weakly discriminating between DVT+PE vs iPE (AUC = 0.66). Conclusion This explorative study suggests an important distinction between PE‐related phenotypes and iDVT when considering clinical and platelet function data. Lower platelet‐dependent TG along with reduced platelet reactivity suggest higher platelet degranulation in PE‐dependent phenotypes compared to iDVT.